Echoes of Grief: The Semiotics of Dove Lamentation in Umayyad Poetry - Ali, Hajir Mahmoud; Sahal, Dilam Kahdim (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2025)
This study investigates the symbolic and semiotic dimensions of the mourning dove in selected Umayyad poetry, focusing on its emotional, cultural, and spiritual connotations. The research is grounded in the problem of how symbols from nature—especially birds—are used to convey complex psychological and emotional states in early Arabic poetic expression. While the dove has appeared across mythological and religious narratives as a symbol of peace, longing, and divine presence, in Umayyad poetry, it often serves as a mirror to human sorrow, particularly in the context of 'Udhrī (chaste) love. The main objective of this study is to explore how the motif of the mourning dove functions as a layered semiotic sign that reflects human grief, nostalgia, and metaphysical yearning. The study employs a qualitative semiotic method based on the frameworks of Roland Barthes and Charles S. Peirce to analyze a selected corpus of Umayyad poems. Through close textual reading and symbol analysis, the research uncovers how poets such as Jamil ibn Ma‘mar and Kuthayyir utilize the image of the dove to construct emotional depth and spiritual symbolism. The findings reveal that the mourning dove operates not only as a literal bird but as a complex signifier of absence, longing, and unattainable love. Its recurring presence reinforces key themes of spiritual suffering and existential melancholy in the Umayyad poetic tradition. This research contributes to broader discussions in Arabic literary criticism, semiotics, and cultural studies by demonstrating how animal imagery, especially that of the dove, serves as a powerful semiotic vehicle in classical Arabic literature